Replanning Criteria and Timing Definition for Parotid Protection-Based Adaptive Radiation Therapy in Nasopharyngeal Carcinoma. (17th December 2015) - Yao, Wei-Rong; Xu, Shou-Ping; Liu, Bo; Cao, Xiu-Tang; Ren, Gang; Du, Lei; Zhou, Fu-Gen; Feng, Lin-Chun; Qu, Bao-Lin; Xie, Chuan-Bin; Ma, Lin
Abstract : The goal of this study was to evaluate real-time volumetric and dosimetric changes of the parotid gland so as to determine replanning criteria and timing for parotid protection-based adaptive radiation therapy in nasopharyngeal carcinoma. Fifty NPC patients were treated with helical tomotherapy; volumetric and dosimetric (D m e a n, V 1, and D 50 ) changes of the parotid gland at the 1st, 6th, 11th, 16th, 21st, 26th, 31st, and 33rd fractions were evaluated. The clinical parameters affecting these changes were studied by analyses of variance methods for repeated measures. Factors influencing the actual parotid dose were analyzed by a multivariate logistic regression model. The cut-off values predicting parotid overdose were developed from receiver operating characteristic curves and judged by combining them with a diagnostic test consistency check. The median absolute value and percentage of parotid volume reduction were 19.51 cm 3 and 35%, respectively. The interweekly parotid volume varied significantly (p < 0.05 ). The parotid D m e a n, V 1, and D 50 increased by 22.13%, 39.42%, and 48.45%, respectively. The actual parotid dose increased by an average of 11.38% at the end of radiation therapy. Initial parotid volume, initial parotid D m e a n, and weight loss rate are valuable indicators for parotid protection-based replanning.